Maladaptation of Right Ventricle to High Pulmonary Hypertension in an Adult Patient with Patent Ductus Arteriosus - Zineb, Mehssani (RA Journal of Applied Research, 2022)
Pulmonary arterial hypertension is an obstructive pulmonary vasculopathy and the RV is considered a major determinant of survival in patients with precapillary pulmonary hypertension. The transition from adaptive to maladaptive phenotype remains poorly understood and clinically unpredictable. Several mechanisms having been suggested in right heart disease but the causes of maladaptive cardiac remodeling remain unknown and require further research. We report the case of PAH in the context of an overlooked patent ductus arteriosus in adulthood with RV consequences.